PENYELESAIAN SENGKETA MELALUI UPAYA (NON LIGITASI) MENURUT PERATURAN PERUNDANG.UNDANGAN - Ahmadi Hasan (Pascasarjana UIN ANTASARI Banjarmasin, 2007)
Solviig rhe dispule through nonlegitimate way is ooly allowed in private Ir,, while in public law it ;s stjll a problen. This is because The Criminal Code does not provide the chance to solve the dispute outside rhe coun. In facq the sourcc of nalional law is westem law, Islarnic law, and faditional law. Sociologically some ethnic goups such as Banjarese still hold traditionat law likc peace tradition in solving the dispute. lt is therefore interesting to observe hor!juridical views this problem.